Biostimulatory Influence of Biochar on Degradation of Petroleum Hydrocarbon Impacted Soil - Michael E. Nkereuwem; Afeez O. Amoo; Adeniyi O. Adeleye; Hafsat S. Abubakar; Victor O. Onokebhagbe; Fatimah Kamaldeen (CV. Literasi Indonesia, 2021)
Soil pollution caused by petroleum hydrocarbon and its derivatives has become a grave global issue. Physico-chemical techniques are often expensive. However, bioremediation of petroleum hydrocarbon polluted soil is cost-effective. Therefore, the study was carried out to assess the biostimulatory influence of biochar on the degradation of petroleum hydrocarbon impacted soil in NNPC Depot, kano state. Soil samples were randomly collected from the polluted site to obtain a composite sample. About 400 g of the polluted soil was filled into pots and arranged in a 2x2 factorial experiment in a completely randomized design with three replications. Bone and wood char was at 2 levels (0 and 50 g/pot) each. Data were collected on the physicochemical properties (pH, TN, and Av. P) of the soil, Total Petroleum Hydrocarbon (TPH), and bacterial population. Data were analyzed using ANOVA at α0. 05. Results obtained from the study show that biochar application significantly (p<0.05) enhanced TPH degradation and bacterial population in the polluted soil. However, Bone char significantly(p<0.05) enhanced TPH degradation and bacterial population the most compared to wood char. Combined bone and wood char application resulted in significantly (p<0.05) lower residual TPH content in the polluted soil compared to using bone or wood char alone. Thus, bone and wood char should be used in the bioremediation of petroleum hydrocarbon impacted soils.